Pemberdayaan Masyarakat dalam Pengelolaan Sumber Air Bersih di Desa Sampean Kabupaten Labuhan Batu Selatan - Simamora, Sri Purwasih; Muniruddin, Muniruddin (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze community empowerment in the management of clean water resources in Sampean Village, Sungai Kanan District, South Labuhan Batu Regency. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. The findings reveal that community empowerment is reflected in regular financial contributions, collective maintenance activities, and active community participation in sustaining clean water resources. Although most residents considered the clean water service adequate, several challenges remain, including uneven community participation, dependence on electric pumps without backup systems, and limited institutional capacity in water resource management. These findings suggest that the sustainability of community-based clean water management depends not only on the availability of infrastructure but also on strengthening local institutions and enhancing community participation. This study provides practical recommendations for village governments and local stakeholders to improve sustainable, community-based clean water management.